Fractional anisotropy and mean diffusivity in the corpus callosum of patients with multiple sclerosis: the effect of physiotherapy - Ibrahim, Ibrahim; Tintera, Jaroslav; Skoch, Antonin; Jirů, Filip; Hlustik, Petr; Martinkova, Patricia; Zvara, Karel; Rasova, Kamila (Neuroradiology, 2011)
INTRODUCTION: Modulation of neurodegeneration by physical activity is an active topic in contemporary research. The purpose of this study was to investigate changes in the brain's microstructure in multiple sclerosis (MS) after facilitation physiotherapy. METHODS: Eleven patients with MS were examined using motor and neuropsychological testing and multimodal MRI at the beginning of the study, with second baseline measurement after 1 month without any therapy, and after a 2-month period of facilitation physiotherapy. Eleven healthy controls were examined at the beginning of the study and after 1 month. Fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (λ (ax)), and radial diffusivity (λ (rad)) were calculated for the whole corpus callosum (CC) in the midsagittal slice of T1W 3D MPRAGE spatially normalized images. Data were analyzed using linear mixed-effect models, paired, and two-sample tests. RESULTS: At the baseline, patients with MS showed significantly lower values in FA (p < 0.001), and significantly higher values in MD (p < 0.001), λ (ax) (p = 0.003), and λ (rad) (p < 0.001) compared to control subjects. The FA, MD, λ (ax), and λ (rad) did not change between the first and second baseline examinations in either group. Differences 2 months after initiating facilitation physiotherapy were in FA, MD, and in λ (rad) significantly higher than differences in healthy controls (p < 0.001 for FA, p = 0.02 for MD, and p = 0.002 for λ (rad)). In MS patients, FA in the CC significantly increased (p < 0.001), MD and λ (rad) significantly decreased (p = 0.014 and p = 0.002), and thus approached the values in healthy controls. CONCLUSION: The results of the study show that facilitation physiotherapy influences brain microstructure measured by DTI.
Keywords: Models, Neurological; Humans; neuropsychologické testy; Case-Control Studies; lidé středního věku; Multiple Sclerosis; modely neurologické; studie případů a kontrol; corpus callosum; Female; dospělí; výsledek terapie; lidé; počítačové zpracování obrazu; Image Processing, Computer-Assisted; zobrazování difuzních tenzorů; Physical Therapy Modalities; Adult; anizotropie; Neuropsychological Tests; ženské pohlaví; roztroušená skleróza; Diffusion Tensor Imaging; Male; Middle Aged; Treatment Outcome; techniky fyzikální terapie; mužské pohlaví; Corpus Callosum; Anisotropy